2006
DOI: 10.1002/jnr.20990
|View full text |Cite
|
Sign up to set email alerts
|

Differential role of presenilin‐1 and ‐2 on mitochondrial membrane potential and oxygen consumption in mouse embryonic fibroblasts

Abstract: Increasing evidence indicates that mitochondrial alterations contribute to the neuronal death in Alzheimer's disease (AD). Presenilin 1 (PS1) and Presenilin 2 (PS2) mutations have been shown to sensitize cells to apoptosis by mechanisms suggested to involve impaired mitochondrial function. We have previously detected active gamma-secretase complexes in mitochondria. We investigated the impact of PS/gamma-secretase on mitochondrial function using mouse embryonal fibroblasts derived from wild-type, PS1-/-, PS2-/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 62 publications
1
39
0
1
Order By: Relevance
“…This suggests that PS2 is involved in the activation of microglia from the surveying stage. Consistent with this phenomenon, Behbahani and colleagues 41 showed that PS2 plays a role in mitochondrial membrane potential activity and cell calcium levels that may result in activity impairment. PS1 associates with microtubules and microfilaments and PS1 dysfunction may reduce cytoskeletal association.…”
mentioning
confidence: 77%
“…This suggests that PS2 is involved in the activation of microglia from the surveying stage. Consistent with this phenomenon, Behbahani and colleagues 41 showed that PS2 plays a role in mitochondrial membrane potential activity and cell calcium levels that may result in activity impairment. PS1 associates with microtubules and microfilaments and PS1 dysfunction may reduce cytoskeletal association.…”
mentioning
confidence: 77%
“…For example, both PS1 and PS2 overexpression in WT and FAD-linked mutants decrease [Ca 2+ ] ER (6) and increase Ca 2+ leak across the ER (although to different extents), but only PS2 strongly inhibits SERCA activity (4, 6) and increases ER-mitochondria tethering. Of interest, along these lines, Behbahani et al (29) showed that mitochondrial functions are reduced significantly in cells from PS2 (but not PS1) knockout animals. This energetic deficit could depend on the reduction of ER-mitochondria Ca 2+ transfer, as elegantly demonstrated recently by Cárdenas et al (30).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, both PS1 and PS2 are found enriched in the so-called mitochondria-associated membranes (MAMs), domains of close apposition between ER and mitochondria [3]. Interestingly, in PS2 KO MEF cells (but not in PS1 KO cells), mitochondrial dysfunctions have been reported, such as reduced mitochondrial membrane potential and lower respiration rate [5]. This energy deficit could indeed depend on the reduction of ER-mitochondria Ca 2+ transfer, due to a decreased organelle apposition caused by the absence of PS2.…”
Section: Characteristics Of Ca 2+ Handling By Mitochondria In Differementioning
confidence: 96%